2017
DOI: 10.1002/2017gl072916
|View full text |Cite
|
Sign up to set email alerts
|

Close packing effects on clean and dirty snow albedo and associated climatic implications

Abstract: Previous modeling of snow albedo, a key climate feedback parameter, follows the independent scattering approximation (ISA) such that snow grains are considered as a number of separate units with distances longer than wavelengths. Here we develop a new snow albedo model for widely observed close‐packed snow grains internally mixed with black carbon (BC) and demonstrate that albedo simulations match closer to observations. Close packing results in a stronger light absorption for clean and BC‐contaminated snow. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…These values are, in fact, closer to the g of large spherical snow grains (g ≈ 0.89) or that of spheroids with an aspect ratio of 0.5 (g ≈ 0.86; Fig. 4 in He et al, 2017b) than that of the OHC. Therefore, should the values derived by Ottaviani et al (2015) be typical of snow, the use of the OHC would tend to overestimate snow albedo.…”
Section: Uncertainties In Snow Albedo Calculationsupporting
confidence: 59%
See 1 more Smart Citation
“…These values are, in fact, closer to the g of large spherical snow grains (g ≈ 0.89) or that of spheroids with an aspect ratio of 0.5 (g ≈ 0.86; Fig. 4 in He et al, 2017b) than that of the OHC. Therefore, should the values derived by Ottaviani et al (2015) be typical of snow, the use of the OHC would tend to overestimate snow albedo.…”
Section: Uncertainties In Snow Albedo Calculationsupporting
confidence: 59%
“…This choice was based on fitting the phase function to measurements of angular scattering by blowing snow. Very recently, He et al (2017b) developed another parameterization for the co-albedo and asymmetry parameter of snow for potential use in snow, land surface, and climate models, based on single-scattering calculations for spheres and three non-spherical shapes. This parameterization can be used for clean as well as dirty snow, as it includes the effects on co-albedo due to black carbon internally mixed with snow.…”
Section: Introductionmentioning
confidence: 99%
“…Light attenuation within the snowpack is related to the density of the scattering elements per unit volume. In addition, layer structure, grain shape, anthropogenic and natural impurities (such as black carbon, dust and algae) and close-packing effects of snow grains affect scattering properties and thus, the albedo of a snowpack (Warren and Wiscombe, 1980;Kokhanovsky and Zege, 2004;Aoki et al, 2011;Kokhanovsky, 2013;Libois et al, 2013;Libois et al, 2014;Komuro and Suzuki, 2015;Peltoniemi et al, 2015;Pirazzini et al, 2015;Räisänen et al, 2015;Cook et al, 2017;He et al, 2017, Kokhanovsky et al, 2018. Several models for the coupled mass and energy balances of snow on the ground have also been developed (Flanner and Zender, 2006;Essery, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies (Hansen and Nazarenko, 2004;Hansen et al, 2005), IPCC (2007) showed the radiative forcing range of 0.10 ± 0.10 W m −2 induced by aerosol in snow at the global scale, whereas IPCC (2013) adopted a radiative forcing of +0.04 (+0.02 to +0.09) W m −2 according to the results of Bond et al (2013). Recent studies have shown the significant impacts of snow grain shape (spherical vs. nonspherical) and aerosol-snow mixing state (internal vs. external) on BC and dust-in-snow radiative forcing (e.g., Flanner et al, 2012;Liou et al, 2014;Dang et al, 2016;He et al, 2017bHe et al, , 2018a. Further studies also show the effects of snow grain packing (He et al, 2017a) and aerosol size distribution in snow (Schwarz et al, 2013;He et al, 2018b) on aerosol-snow interactions.…”
Section: Introductionmentioning
confidence: 99%